Fasting Plasma Glucose as a Primary Screening Test for the Diagnosis of Gestational Diabetes mellitus: Fasting Plasma Glucose and Gestational Diabetes mellitus (Journal of the Medical College for Women & Hospital, 2025)
Aim: To see the diagnostic efficacy of fasting plasma glucose (FPG) compared to Oral Glucose Tolerance Test (OGTT) during pregnancy.Materials and Method: In this cross-sectional study, we enrolled 542 pregnant women 18 years or older by consecutive sampling irrespective of gestational age. Three-sample 75-gm OGTT was done and categorized  into either normal glucose tolerance (NGT) ,abnormal glucose tolerance ( AGT) according to WHO 2013 criteria.Results: The sensitivity of FPG with a threshold of 5.1mmol/L was 47.3% among the study subjects, which was very low but specificity was very high (99.7%). However, changing the cut-off value to 4.7mmo/L and 4.5mmol/L significantly increased the sensitivity to 64.8% and 73.3% with modestly decreased specificity to 86.2% and 73.2% respectively. In pregnant women with gestational age 24 to 28 weeks, FPG with a threshold of 4.5mmol/L could identify 75% of Gestational Diabetes Mellitus (GDM)  subjects with specificity of 76.8%. Furthermore, it has the highest sensitivity in detecting AGT in all three trimesters (80%, 74.4% and 68%) compared to 4.7mmol/L (80%, 68.9% and 50%) and 5.1 mmol/L (80%, 47.8% and 30%) in 1st, 2nd and 3rd trimester respectively. FPG had a positive correlation with maternal age (r=0.138, p=0.001), and Body Mass Index (BMI) (r=0.164, p